Low levels of serum vitamin C in children with limb fractures: a case-control study - Ding, Yangkun; Wang, Chunhua; Yu, Jiazhi; Lu, Mingzhu; Mu, Pengfei; Liu, Xiangfei; Liu, Tao (Frontiers in Pediatrics, 2023)
The role of vitamin C in pediatric fractures has not received much attention, although it is known to be a factor in osteoporotic fractures in the elderly. This case-control study aimed to investigate the changes in serum vitamin C levels among children with limb fractures.We recruited 325 children with and 316 children without limb fractures hospitalized between January 2021 and December 2021. Following admission, basic demographic data of all participants were collected, and fasting serum vitamin C levels were determined using ultra-highperformance liquid chromatography-tandem mass spectrometry.The mean age of the fracture group was 5.1 years (95% CI, 4.83-5.33) . The serum vitamin C levels in the fracture group (4.48 µg/mL) were significantly lower than those in the control group (8.38 µg/mL) (p < 0.0001). Further subgroup analysis of the fracture group revealed that serum vitamin C levels decreased significantly after 4 years of age and there was a significant difference in the duration after injury between < 6 and > 6 h (p = 0.0224). Spearman's rank correlation coefficient suggested that age and vitamin C levels were negatively correlated in the fracture group.In general, children with limb fractures had lower serum vitamin C levels, especially those aged 4 years and over.